Peran Pengurus Panti Asuhan dalam Menunjang Keberlanjutan Pendidikan Anak di Panti Asuhan An-Nur Pasanehan Candung - Adinda Adinda; Yeni Afrida (Journal Innovation In Education, 2024)
This study seeks to ascertain the role of administrators in facilitating children's educational aspirations, the challenges experienced by administrators in fulfilling their responsibilities, and the strategies used by administrators to overcome these challenges. The investigation used the descriptive technique. The used data collecting strategies include direct observation, direct communication, and documentary research. The corresponding data collection instruments include observation, interviews, and documentation. The study analysis was conducted in a qualitative descriptive fashion, including a total of 23 participants. These participants included 2 administrators from orphanages, 4 foster children from vocational schools, 16 foster children from middle schools, and 1 foster kid from an elementary school. Orphanage administrators have a crucial role in ensuring the uninterrupted education of children. They serve as motivators, facilitators, guides, and surrogate foster parents for the children's families or parents. The challenges faced by administrators in implementing the programme stem from the youngsters themselves and the availability of financing. The management is addressing the current difficulties by engaging with the children, seeking donors to provide financial support for the institution, and ensuring that all the requirements of the children at the orphanage are met.